Pengaruh Word of Mouth dan Brand Image Terhadap Keputusan Pembelian dan Kepuasan Konsumen Restaurant Tradisional Pekanbaru - Dian Pratiwi; Maha Martabar Mangatas Lumbanraja; Rahmat Junaidi (Forum Kerjasama Pendidikan Tinggi, 2023)
The culinary industry in Indonesia, especially in the city of Pekanbaru, will be increasingly competitive every year. With increasingly competitive competition, culinary business actors must change their business orientation from product centric to customer centric, namely not only focusing on serving delicious food but also maintaining customer satisfaction in a holistic manner. Word of Mouth and Brand Image are believed to be able to influence purchasing decisions so as to create customer satisfaction. The purpose of this study was to determine the effect of Word of Mouth and Brand Image on Purchasing Decisions and Consumer Satisfaction in Legendary Culinary in Pekanbaru. This study uses a quantitative approach. The sample in the study were 112 people who had made purchases at one of the research objects, namely Pondok Patin HM Yunus, Kim Teng Coffee Shop, Paku Onen Ketupat Gulai Shop, and Pak Jenggot's Cendol Ice. Sampling using non-probability sampling method and convenience sampling technique. The research instrument used a questionnaire and was analyzed using Structural Equation Modeling (SEM) with the Partial-Least Square approach (PLS-SEM). The results of this study indicate that there are differences in the results of the influence of Brand Image (positive) and Word of Mouth (negative) on Decision Purchase. Purchasing decisions have a positive effect on consumer satisfaction and mediate the influence of Word of Mouth and Brand Image on consumer satisfaction with purchasing decisions as an intervening variable. With this research, it is hoped that traditional restaurants will be able to maintain the Generation X market and penetrate the Generation Y and Z markets which are more technologically adaptive.